Disciplinary boundaries and climate change education: teachers' conceptions of climate change education in the Philippines and Singapore - Ho, Li-Ching; Seow, Tricia (International Research in Geographical and Environmental Education, 2017)
This qualitative study examines how climate change scientific knowledge is framed and positioned within the Singapore and Philippines school curricula in relation to broader citizenship concepts and ideas. The findings reveal that climate change is taught in very different ways within both education systems. The Singapore case demonstrates the strengths and limitations of relying on one discipline such as geography as the sole vehicle for teaching such a complex socio-scientific issue. The Philippines case, on the other hand, provides an indication of the advantages and constraints to engaging the issue of climate change from an interdisciplinary social studies perspective.
openalex: W2616054366 mag: 2616054366
Keywords: C:Philippines; C:Singapore; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12545 Education for Global Citizenship in a Globalized World; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:yes